Few large trees, rather than plant diversity and composition, drive the above-ground biomass stock and dynamics of temperate forests in northeast China - Yuan, Zuoqiang; Ali, Arshad; Sanaei, Anvar; Ruiz-Benito, Paloma; Jucker, Tommaso; Fang, Lei; Bai, Edith; Ye, Ji; Lin, Fei; Fang, Shuai; Hao, Zhanqing; Wang, Xugao (Forest ecology and management, 2021)
•The AGB of top 1% trees is a better proxy than plant diversity for AGB dynamic.•Secondary forest has higher AGB gain, net change, but lower loss than intact forest.•Topography regulates the structure, composition and AGB dynamic of temperate forest. Large trees, as the versatile provider of ecosystem services, are the most susceptible to episodic disturbance regimes such as extreme climate and biotic agents across the globe, and hence, largely determine forest demographic processes. Despite the recognized fundamental ecological significance of large-diameter trees to above-ground biomass (AGB) stock, relatively little is known about their distinctive role, interplaying with abiotic and biotic drivers, in shaping forest AGB dynamics (i.e., gain and loss) at regional or larger extents. Here, we hypothesized that the AGB of few large trees drives AGB stock and dynamics (gain and loss) better than species diversity and trait composition in temperate forests along topography and soil gradients. We analyzed two repeated forest inventories data from 700 plots (including 74,300 adult trees) across 15 plots in temperate forests of northeastern China, including old-growth and disturbed forests. A steady net AGB change increase was found for 13 of the 15 plots. Despite disturbed forests were recovering from post-logging disturbance with a lower density of large-diameter trees and AGB stock than old-growth plots, disturbed forests had higher AGB gain, net AGB change and lower AGB loss than old-growth forests. The largest trees (i.e. top 1% AGB or diameter) were consistently more important for explaining AGB stock, gain and loss compared to plant diversity and trait composition. Besides, the elevation-related topographic factors were more direct determinants of forest AGB accumulation than soil nutrients, and also exerted the indirect impacts via increasing the dominance of resource-conservative trees, stand structural diversity and top 1% large trees. Overall, we highlight the key overruling effect of top 1% large trees on AGB stock and dynamics in response to local environmental factors. This study could improve our understanding of the multiple ecological mechanisms underlying the global change drivers of forest AGB stock and dynamics.